Impact of Freebies on Buying Intention of Customers' in the Food Industry - Veena Balachandran (International Journal of Advanced Science and Technology, 2020)
With the advent of Government missions like Startup India, ASPIRE, Atal Innovation Mission, eBiz Portal, Multiplier Grants Scheme, The Venture Capital Assistance Scheme and many more, India is a host to more than 7,200 start-ups as of 2019 and food start-ups alone have raised 512 million as an investment in the same year. In a competitive market like this, the survival strategy and execution of the same is crucial since 90% of Indian start-ups fail within the first 5 years of inception.  As a result of which, many start-ups adopt strategies and practices to get an edge over their competitors. According to Banerjee’s study in 2009, one of the many but most often used marketing strategies by start-ups is giving away freebies. This paper aims to address the impact freebies have on buying intention of the customer, particularly in the food industry. The theoretical framework of the paper revolves around the fact that freebies are adopted by start-ups as a marketing tool to attract more walk-in customers, increase sales, create trust, loyalty and thereby act as a catalyst in brand building. However, how often customers buy from a particular brand if not for their freebies is speculative. The results of the study help us understand whether freebies influence buying intention that leads to more sales and whether food start-ups, despite their early-stage financial struggle, should opt for freebies as a marketing tool to attract more customers.Keywords: Buying intention, Food Start-ups, Freebies